2015
DOI: 10.4238/2015.june.9.5
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly and characterization of the root transcriptome and development of simple sequence repeat markers in Paphiopedilum concolor

Abstract: ABSTRACT. Paphiopedilum orchids (Orchidaceae) have attracted much attention from botanists and horticulturists because of their peculiar leaves and beautiful flowers. Furthermore, the dry roots of Paphiopedilum plants have well-known medicinal uses. However, it is unknown how sensitive and plastic the root genes are to environmental changes or how these environmental changes regulate the biosynthesis of active ingredients. In this study, we chose Paphiopedilum concolor for root sequencing, as it is widely used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…On average, one SSR loci was found for every 5.42 kb in a unigene, which corresponded to an SSR frequency of 13.06%. The SSR frequency was more than 7.58% of Paphiopedilum concolor (Bateman) Pfitzer (Li et al, 2015b) and consistent with the dicotyledonous SSR frequencies of 2.65-16.82% (Kumpatla and Mukhopadhyay, 2005). The largest fraction of repeat motif was mononucleotide (41.87%), followed by dinucleotide (39.13%) and trinucleotide (18.36%), while tetranucleotide, pentanucleotide and hexanucleotide were just very few numbers of <1% altogether.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…On average, one SSR loci was found for every 5.42 kb in a unigene, which corresponded to an SSR frequency of 13.06%. The SSR frequency was more than 7.58% of Paphiopedilum concolor (Bateman) Pfitzer (Li et al, 2015b) and consistent with the dicotyledonous SSR frequencies of 2.65-16.82% (Kumpatla and Mukhopadhyay, 2005). The largest fraction of repeat motif was mononucleotide (41.87%), followed by dinucleotide (39.13%) and trinucleotide (18.36%), while tetranucleotide, pentanucleotide and hexanucleotide were just very few numbers of <1% altogether.…”
Section: Discussionsupporting
confidence: 73%
“…1). The most abundant trinucleotide repeat type was CCG/CGG, such as P. concolor (Li et al , 2015b), which commonly found in monocots (Wang et al , 2011). In contrast, there was no CG/CG repeat identified, which infrequent in plant transcriptome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, root transcriptome from Paphiopedilum concolor was also produced to explore genes involved in orchid root development (Li et al 2015b ). Over 1195 unique genes participating in secondary metabolic pathways, and 609 ESTs involved in plant hormone biosynthesis, and plant signal transduction were revealed.…”
Section: Orchid Genome Evolutionmentioning
confidence: 99%
“…Many calcicoles (species adapted to calcareous soil) have evolved in the region, and their habitats and niches have long been regarded as ‘natural laboratories’ for ecological and evolutionary studies to understand natural selection and species evolution because of the high diversity and unique biota ( Clements et al, 2006 ). Unfortunately, previous studies on karst-specific species are scarce ( Kang et al, 2014 ; Ai et al, 2015 ; Li et al, 2015 ; Liu et al, 2019 ; Feng et al, 2020 ), and until now, the mechanisms of karst environmental adaptation have rarely been examined. Yet such information is important for understanding the survival and adaptive strategies of species in the special karst environmental conditions.…”
Section: Introductionmentioning
confidence: 99%